Implications of the New US Cholesterol Guidelines in the Brazilian Longitudinal Study of Adult Health (ELSA‐Brasil) - Bittencourt, Marcio Sommer (Clin Cardiol, 2016)
BACKGROUND: The new US guidelines for the primary prevention of cardiovascular disease have substantially changed the approach to hyperlipidemia treatment. However, the impact of those recommendations in other populations is limited. In the present study, we evaluated the potential implications of those recommendations in the Brazilian population. HYPOTHESIS: The new U.S. recommendations may increase the proportion of individuals who are candidates for statin therapy. METHODS: We included all participants of the Brazilian Longitudinal Study of Adult Health (ELSA‐Brasil) without known cardiovascular disease. We calculated the indication for statin therapy according to the current Brazilian recommendations and the new US guidelines, using both the 5.0% and the 7.5% risk cutoffs to recommend treatment, and compared their impact in the Brazilian population stratified by age, sex, and race. RESULTS: Although the current guidelines would recommend treatment for 5499 (39.1%) individuals, the number of individuals eligible for statin therapy increased to 6014 (42.7%) and to 7130 (50.7%) using the 7.5% and 5% cutoffs, respectively (P < 0.001). This difference is more pronounced for older individuals, and virtually all individuals age >70 years would be eligible for statins, whereas the new guidelines would reduce the number of candidates for statin therapy in individuals age <45 years. CONCLUSIONS: The application of the new US guidelines for the use of lipid‐lowering medications in a large middle‐aged Brazilian cohort would result in a significant increase in the population eligible for statins. This is largely driven by males and older individuals. Additional cost‐effectiveness analyses are needed to define the appropriateness of this strategy in the Brazilian population.